The Influence of Purchase Motivation on Perceived Preference Uniqueness and Assortment Size Choice - Whitley, Sarah C; Trudel, Remi; Kurt, Didem (Journal of Consumer Research, 2018)
Abstract The present research examines how hedonic and utilitarian purchase motivations influence consumers’ perceptions of their product preferences and the resulting number of options they wish to consider when making a purchase. Across six studies, consumers choose to review larger assortments when their purchase motivation is hedonic rather than when their purchase motivation is utilitarian. This effect occurs because consumers with hedonic purchase motivations perceive their product preferences as highly unique compared to consumers with utilitarian purchase motivations. Higher perceived preference uniqueness increases the difficulty consumers anticipate in finding a preference-matching product, resulting in an expansion of the number of product alternatives to review. Further supporting the perceived preference uniqueness account, the documented effect is attenuated when product assortments are customized based on consumers’ personal preferences and when a social similarity priming task is employed. These findings provide additional evidence on the distinction between hedonic and utilitarian purchase motivations, their impact on perceived preference uniqueness, and their implications for consumer decision making via assortment size choice.